2013
DOI: 10.1182/blood-2012-06-434803
|View full text |Cite
|
Sign up to set email alerts
|

The polygenic nature of inhibitors in hemophilia A: results from the Hemophilia Inhibitor Genetics Study (HIGS) Combined Cohort

Abstract: Key Points• The data demonstrate the complexity of the genetic contribution to inhibitor development in people with hemophilia A.• Potentially decisive markers have been identified, indicating the importance of further evaluation of intracellular signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 47 publications
5
67
2
1
Order By: Relevance
“…Allele and genotype frequencies were similar to those previously described. 31 No significant association between the genotypes or the individual allele frequencies, and the development of inhibitors was observed, in agreement with a recently published genome-wide association study by Astermark et al 32 (Online Supplementary Table S1; P>0.05).…”
Section: Single Nucleotide Polymorphismssupporting
confidence: 79%
See 1 more Smart Citation
“…Allele and genotype frequencies were similar to those previously described. 31 No significant association between the genotypes or the individual allele frequencies, and the development of inhibitors was observed, in agreement with a recently published genome-wide association study by Astermark et al 32 (Online Supplementary Table S1; P>0.05).…”
Section: Single Nucleotide Polymorphismssupporting
confidence: 79%
“…The authors identified 53 single nucleotide polymorphisms as significant predictors of inhibitor status, thus highlighting the complexity of the anti-FVIII immune response. 32 However, the genome-wide association study did not find associations of single nucleotide polymor-HMOX1 promoter polymorphism and FVIII inhibitors haematologica | 2013; 98 (10) 1653 Table 2. HO-1 (GT) n microsatellite distribution in patients with hemophilia A. phisms located in the promoter of the HMOX1 gene with the inhibitor status of the patients, which is in agreement with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlighted the complexity of the genetic polymorphisms that might modulate antibody responses against FVIII and FIX. 40 …”
Section: Fviii Haplotypesmentioning
confidence: 99%
“…Polymorphisms in other immune related gene such as CTLA-4, DOCK2, MAPK9, PTPRR and CD36 gene have also been linked to inhibitor development [41,42]. In a recent study by Astermark (2013), 53 SNPswere reported to be the predictors of inhibitor status, further indicating the complexity of immune response and immune modifier genes in the development inhibitors [43].…”
Section: Hla and Immune Related Genes In Inhibitor Productionmentioning
confidence: 99%